2023
DOI: 10.1080/19490976.2022.2164152
|View full text |Cite|
|
Sign up to set email alerts
|

Human milk oligosaccharides, antimicrobial drugs, and the gut microbiota of term neonates: observations from the KOALA birth cohort study

Abstract: The infant gut microbiota affects childhood health. This pioneer microbiota may be vulnerable to antibiotic exposures, but could be supported by prebiotic oligosaccharides found in breast milk and some infant formulas. We sought to characterize the effects of several exposures on the neonatal gut microbiota, including human milk oligosaccharides (HMOs), galacto-oligosaccharides (GOS), and infant/maternal antimicrobial exposures. We profiled the stool microbiota of 1023 one-month-old infants from the KOALA Birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Parity was also associated with maternal gut microbiota composition. The effect of parity or older siblings on infant microbiota has been observed previously 2 , 17 , 18 , 45 and it is mainly believed to reflect the added microbial exposures from the older siblings. Recently, infants with older siblings were found to have a more mature gut microbiota at 1 year, which in turn was associated with a lower prevalence of food allergy.…”
Section: Discussionmentioning
confidence: 78%
“…Parity was also associated with maternal gut microbiota composition. The effect of parity or older siblings on infant microbiota has been observed previously 2 , 17 , 18 , 45 and it is mainly believed to reflect the added microbial exposures from the older siblings. Recently, infants with older siblings were found to have a more mature gut microbiota at 1 year, which in turn was associated with a lower prevalence of food allergy.…”
Section: Discussionmentioning
confidence: 78%
“…It is possible that elevated abundance of Bifidobacteria that use short-chain HMOs might outcompete Akkermansia. Clostridium_sensu_stricto , a bacterium which had the highest abundance in MFM mice, has been positively associated with antibiotic exposure during infancy ( 46 ). Interestingly, HMOs supplementation in these mice significantly reduced the abundance of this microbe, suggesting a potential beneficial effect of HMOs in formula-fed infants.…”
Section: Discussionmentioning
confidence: 99%
“…A proof-of-concept study proved that HMOs selectively enrich the growth of beneficial bacteria, including Bifidobacterium and Bacteroides (Marcobal et al 2011 ). In a large-scale study of 1023 infants, HMOs showed natural variations and influenced the GM of infants (Barnett et al 2023 ). Lacto-N-hexaose and 6′-sialyllactose were positively and negatively associated with the abundance of Bifidobacterium , respectively (Barnett et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a large-scale study of 1023 infants, HMOs showed natural variations and influenced the GM of infants (Barnett et al 2023 ). Lacto-N-hexaose and 6′-sialyllactose were positively and negatively associated with the abundance of Bifidobacterium , respectively (Barnett et al 2023 ). Additionally, the variable composition of HMOs can be explained by maternal genotype, including the secretor (FUT2) and Lewis (FUT3) genes, which, notably, do not drive major differences in the GM between infants (Barnett et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation